2021
DOI: 10.7860/jcdr/2021/46334.15327
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Autologous Blood and Fibrin Glue for Adhering Conjunctival Autografts after Pterygium Excision- A Randomised Clinical Trial

Abstract: Introduction: Fibrin glue is a biological tissue adhesive and acts on the principle of final stages of the coagulation cascade. The cost of commercially available products is very high and not affordable for the patients of low socio-economic strata. As an alternative, pterygium surgery was done using patient’s own blood to adhere the conjunctival autograft to scleral bed by the process of coagulation of fibrin from the oozing blood from the blood vessels under the flap. Aim: To compare autologous blood and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“… 10 , 13 , 26 , 27 In brief, the majority of studies harvested the CAU from the superotemporal quadrant of the bulbar conjunctiva, seven of which reported the use of conjunctival limbal autograft to include part of the superficial limbus. 10 , 12 , 13 , 17 , 18 , 24 , 27 Aside from one study that reported the use of autologous fibrin glue, 20 the fibrin glues used in the studies were commercially available products such as Tisseel ® (Baxter Healthcare Corporation, Glendale, CA) and FIBINGLURAAS ® (Shanghai RAAS Blood Products Co., Ltd, China). In the majority of the studies assessing CAU with sutures, the graft was anchored to the episclera and attached to the adjacent conjunctiva with interrupted 8–0 Vicryl sutures or 10–0 nylon sutures.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 10 , 13 , 26 , 27 In brief, the majority of studies harvested the CAU from the superotemporal quadrant of the bulbar conjunctiva, seven of which reported the use of conjunctival limbal autograft to include part of the superficial limbus. 10 , 12 , 13 , 17 , 18 , 24 , 27 Aside from one study that reported the use of autologous fibrin glue, 20 the fibrin glues used in the studies were commercially available products such as Tisseel ® (Baxter Healthcare Corporation, Glendale, CA) and FIBINGLURAAS ® (Shanghai RAAS Blood Products Co., Ltd, China). In the majority of the studies assessing CAU with sutures, the graft was anchored to the episclera and attached to the adjacent conjunctiva with interrupted 8–0 Vicryl sutures or 10–0 nylon sutures.…”
Section: Resultsmentioning
confidence: 99%
“…All studies were randomized controlled trials aside from four prospective comparative studies. [10][11][12][13] Eight studies compared the use of fibrin glue versus sutures, 12,[14][15][16][17][18][19][20] six studies compared CAU with fibrin glue to other treatment arms, 11,[21][22][23][24][25] and four studies compared CAU with sutures to other treatment arms. 10,13,26,27 In brief, the majority of studies harvested the CAU from the superotemporal quadrant of the bulbar conjunctiva, seven of which reported the use of conjunctival limbal autograft to include part of the superficial limbus.…”
Section: Operative Time: Pterygium Excision With Cau Versus Tissuetuc...mentioning
confidence: 99%
See 1 more Smart Citation